Two-Step Phase Retrieval Algorithm Using Single-Intensity Measurement - Cheng Zhang; Meiqin Wang; Qianwen Chen; Dong Wang; Sui Wei (International Journal of Optics)
Aiming at the problem that the single-intensity phase retrieval method has poor reconstruction quality and low probability of successful recovery, an improved method is proposed in this paper. Our method divides the phase retrieval into two steps: firstly, the GS algorithm is used to recover the amplitude in the spatial domain from the single-spread Fourier spectrum, and then the classical GS algorithm using two intensity measurements (one is recorded and the other is estimated from the first step) measurements is used to recover the phase. Finally, the effectiveness of the proposed method is verified by numerical experiments.